Increased plasma Interleukin-1β level is associated with memory deficits in type 2 diabetic patients with mild cognitive impairment. (October 2018) - Tian, Sai; Huang, Rong; Han, Jing; Cai, Rongrong; Guo, Dan; Lin, Hongyan; Wang, Jiaqi; Wang, Shaohua
Highlights: The first to link plasma IL-1β to Aβ and cognitive performances in T2DM patients. High plasma IL-1β level and low MoCA score in poor blood glucose control patients. Negative association of plasma IL-1β level with memory function in MCI group. High plasma IL-1β level, an independent risk factor for MCI in T2DM patients. Abstract: Type 2 diabetes mellitus (T2DM) and mild cognitive impairment (MCI) are both chronic inflammatory diseases. We aimed to investigate the association of plasma Interleukin-1β (IL-1β) levels with the risk of MCI in T2DM patients. We divided recruited T2DM patients into two groups, MCI group and healthy-cognition controls, according to Montreal Cognitive Assessment (MoCA) scores. Demographic characteristics, clinical parameters and neuropsychological tests were examined. We recruited 202 T2DM patients in this study, including 94 MCI and 108 healthy-cognition controls. T2DM patients with MCI exhibited increased plasma IL-1β and decreased amyloid-β 42 (Aβ42) levels compared to the controls (all p < 0.05). After adjusting fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), homeostasis model assessment of insulin resistance (HOMA-IR) and Aβ42, plasma IL-1β levels were negatively correlated with MoCA and AVLT delayed recall scores, which represented memory function. Multivariable logistic regression model showed that high plasma IL-1β level and low plasma Aβ42 level were correlated with increased risk for MCI in T2DM patients. Increased plasma IL-1β level was significantly associated with MCI in T2DM patients, especially memory deficits. Our findings will provide additional insights into the inflammation pathogenesis of cognitive impairments in T2DM.